PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN SIKAP GOTONG ROYONG KELAS 3A DI SD NEGERI LEDOK 02 SALATIGA - Windy Oktavia; Adi Winanto (STKIP Subang, 2023)
This study aims to improve students' mutual cooperation attitude through the application of Cooperative Learning Model Type Numbered Heads Together (NHT). This research is a Classroom Action Research (PTK) with two cycles. The research subjects were students of grade 3A of SD Negeri Ledok 02 Salatiga, with a total of 18 students. Data collection techniques in this study were observation, questionnaires, and documentation. The results of classical completeness of mutual cooperation attitude in cycle I reached 59.9% with the category not yet seen, in the second cycle classical completeness reached 80.2% with the category of culture. Based on the results of the study, it can be concluded that the attitude of mutual cooperation in students can increase using the Numbered Heads Together (NHT) type learning model. The results of this study can contribute to the world of education as an alternative to solving problems in the affective domain, especially in the attitude of mutual cooperation.